2011
DOI: 10.4103/1596-3519.84701
|View full text |Cite
|
Sign up to set email alerts
|

Perforated appendicitis in a septuagenarian

Abstract: Appendicitis in the elderly is becoming an increasingly frequent clinical encounter due to the increased life expectancy in the human race over the last half-century. Appendicitis in this age group has, therefore, become relatively more common with an atypical presentation that incurs delay in diagnosis with attendant morbidity and mortality. We present a septuagenarian who presented atypically with a rapidly progressing feature of appendicitis that emphasizes the need for early operative intervention. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Total ESBL positivity was detected as 9 (31.2%) and 6 (33.3%) in pediatric and adult patients, respectively. In most of the studies, it was found to be more common in elderly patients having mental confusion, obesity or immune-specific condition and it was responsible for the high incidence of generalized peritonitis and mortality and the mortality and morbidity rate of appendicitis were reported as 2 to 14%, and 40% in elderly patients, respectively [7,[10][11][12][13]. In the present study, the age range of adult patients was 18 to 65 y.…”
Section: Discussionmentioning
confidence: 50%
“…Total ESBL positivity was detected as 9 (31.2%) and 6 (33.3%) in pediatric and adult patients, respectively. In most of the studies, it was found to be more common in elderly patients having mental confusion, obesity or immune-specific condition and it was responsible for the high incidence of generalized peritonitis and mortality and the mortality and morbidity rate of appendicitis were reported as 2 to 14%, and 40% in elderly patients, respectively [7,[10][11][12][13]. In the present study, the age range of adult patients was 18 to 65 y.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, they can present with changes in bowel habits in the form of diarrhea or constipation [14,15]. In addition, they can present with pain in atypical locations, such as left-sided abdominal pain or peri-umbilical abdominal pain radiating to the left side of the umbilicus [16,17].…”
Section: Nausea or Vomitingmentioning
confidence: 99%